Lost in Translation: Unraveling Grammatical Interference in Students’ Writing - Fadilla Taslim; Hendrisman; Refnawati; Desfi Yenti; Afdaleni; Paramitha Suryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study addressed the grammatical interference of Indonesian (L1) in the English (L2) writing of English as Foreign Language (EFL) students. The purpose of this study was to identify the types of Indonesian grammatical interference that occur in the writing of EFL students and to examine the factors that contribute to its occurrence. A descriptive qualitative design was employed. The participants were fourth-semester students of the English Study Program at STKIP Yayasan Abdi Pendidikan who were enrolled in the Scientific Writing course during the 2024/2025 academic year. Data were collected through a writing test, a semi-structured interview, and classroom observation, and were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing and verification. The findings reveal that the students’ L1 grammar continued to influence their L2 writing and that grammatical interference occurred in two categories: syntactical interference and morphological interference. Within syntactical interference, prepositions produced the greatest number of errors, followed by word order, while within morphological interference, the omission of determiners was the most frequent error, followed by singular–plural forms and the be-form. The observation and interviews indicated that the interference stemmed primarily from the structural differences between English and Indonesian grammar, compounded by the students’ habit of composing their ideas in Indonesian first and then translating them into English, together with their limited mastery of English vocabulary and grammar. The study concludes that reducing grammatical interference requires contrastive, form-focused instruction that explicitly addresses the structural gaps between the two languages. Keywords: EFL Writing, Grammatical Interference; Higher Education; L1–L2 Differences; Language Transfer